1992
DOI: 10.1172/jci116134
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors and biologic response in rat parathyroid tissue and C cells.

Abstract: The expression of the PTH and calcitonin genes is dramatically decreased by 1,25(OH)2D3 in vivo, and the PTH gene expression is increased by hypocalcemia. We have now studied the effect of estrogens on the expression of these genes in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…The stimuli which lead to increased PTH gene expression, translation and secretion are well characterized. In vivo, these include low calcium, high phosphate and estrogens (2)(3)(4). The factors which lead to decreased PTH gene expression in vivo are 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) (5) and low phosphate (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimuli which lead to increased PTH gene expression, translation and secretion are well characterized. In vivo, these include low calcium, high phosphate and estrogens (2)(3)(4). The factors which lead to decreased PTH gene expression in vivo are 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) (5) and low phosphate (3).…”
Section: Introductionmentioning
confidence: 99%
“…The integrity of the RNA and the uniformity of RNA transfer to the membrane were determined by UV visualization of the ribosomal RNA bands of the gels and the filters. The filters were fixed by UV cross-linking and hybridized as previously described (4,5). Hybridization was to a random primed rat PTH cDNA (a gift of H. Meyer, GBF, Braunschweig, Germany) and 18S RNA (gift of M. A. Levine, Baltimore, MD).…”
Section: Introductionmentioning
confidence: 99%
“…Parafollicular C cells secrete a polypeptide hormone, calcitonin. Previously, it has been demonstrated that calcitonin gene expression is elevated in response to estrogen, suggesting the presence of an estrogen receptor (ER; Naveh-Many et al 1992). Immunohistochemical studies using monoclonal antibody revealed that ERb, but not ERa, was detected in normal human thyroid follicular and parafollicular C cells (Taylor & Al-Azzawi 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Because estrogen does not affect intestinal VDR content (169), these data support the hypothesis for a vitamin D-independent action of estrogen on intestinal Ca absorption (168). Estrogen receptors are present in parathyroid tissue and thyroid C cells, and treatment of ovariectomized rats with 17|3-esti*adiol stimulates expression of the mRNAs for PTH and CT (170). The combined anabolic effects of PTH and CT on bone provide an indirect pathway for estrogen action in prevention of bone loss (170).…”
Section: Gender and Sex Hormone Effects On Factors Involved In Regulamentioning
confidence: 68%
“…Estrogen receptors are present in parathyroid tissue and thyroid C cells, and treatment of ovariectomized rats with 17|3-esti*adiol stimulates expression of the mRNAs for PTH and CT (170). The combined anabolic effects of PTH and CT on bone provide an indirect pathway for estrogen action in prevention of bone loss (170).…”
Section: Gender and Sex Hormone Effects On Factors Involved In Regulamentioning
confidence: 99%